The IASP classification of chronic pain for ICD-11 - chronic secondary visceral pain - Aziz, Qasim; Giamberardino, Maria; Barke, Antonia; Korwisi, Beatrice; Baranowski, Andrew; Wesselmann, Ursula; Rief, Winfried; Treede, Rolf-Detlef (Pain, 2019)
AbstractChronic visceral pain is a frequent and disabling condition. Despite high prevalence and impact, chronic visceral pain is not represented in ICD-10 in a systematic manner. Chronic secondary visceral pain is chronic pain secondary to an underlying condition originating from internal organs of
Gesehen am 27.06.2019